Analysis for Overburden Destruction on Lateral Boundary of Stope Based on Viscoelastic-Plastic Finite Element Method - Zengde Yin; Jinxiao Liu; Yongle Liu; Wenxin Li (Advances in Civil Engineering)
In longwall mining, the deformation and destruction of overlying strata always lag behind coal extraction. The overlying strata characteristics at the lateral boundary of the stope can be classified into four categories, i.e., Hard-Soft, Soft-Hard, Hard-Hard, and Soft-Soft. In order to analyze the effect of the above four structures, we adopt viscoelastic theory to the finite element method (FEM) and define the point safety factor to evaluate the rock damage. The accuracy of programming is verified through example verification. A modified viscoelastic-plastic FEM model is applied to analyze the performance of four overburden structures. The numerical computation results show the following: From the rupture of overburden rock to its stabilization, the duration time of four typical structures can be sorted as “Soft-Soft < Hard-Soft < Soft-Hard < Hard-Hard”. The fracture direction and dip angle of each structure vary as well. The fracture zone of the H-S structure is inclined toward the goaf, while that of the S-H structure is inclined to the lateral boundary of the stope. The fracture zone of the H-H structure is also inclined toward the lateral boundary, with a greater angle than the S-H structure, while the fracture zone of the S-S structure is inclined to goaf, with a greater angle than the H-S structure.